Improving the Biopharmaceutical Properties of Cannabinoids in Glioblastoma Multiforme Therapy With Nanotechnology: A Drug Delivery Perspective - Walker, Stephanie B. [UNESP]; Duarte, Jonatas L. [UNESP]; Di Filippo, Leonardo D. [UNESP]; Chorilli, Marlus [UNESP] (Wiley, 2024)
Glioblastoma multiforme (GBM) is the most prevalent primary brain tumor in adults and is known for its rapid proliferation and infiltrative nature. Current therapeutic strategies include surgical resection followed by radio- and chemotherapy. Still, they are hindered by GBM biological characteristics and physical-chemical properties of chemotherapeutic drugs, leading to limited efficacy and poor prognosis. Cannabinoids have emerged as potential anti-GBM agents, exhibiting antiangiogenic, antimetastatic, and antiproliferative effects. However, their hydrophobicity and poor oral bioavailability pose significant challenges for clinical applications. This study evaluates the potential of nanocarriers in enhancing the solubility and targeted delivery of cannabinoids for GBM therapy. The innovative combination of nanotechnology with cannabinoid-based treatment offers a promising strategy to improve therapeutic outcomes. We addressed the application of nanocarriers to deliver cannabinoids, which can enhance passage across the blood-brain barrier and enable targeted therapy. Studies demonstrate the potential of nanocarriers in improving solubility, stability, and controlled release of cannabinoids, highlighting the advancements in nanocarrier design for optimized delivery to glioma cells. Cannabinoids can exert their antitumor effect, including the induction of apoptosis through the ceramide and p8-regulated pathways and the modulation of immune responses. The evidence found in this study supports the potential of cannabinoid-based nanotechnologies in GBM therapeutic regimens as a strategy to enhance its efficacy and patient outcomes.
Keywords: brain cancer; Cannabis sativa; glioma; nanotechnology; terpenoids